Avaliação do estresse oxidativo, estado nutricional e vitaminas lipossolúveis em crianças atendidas no ambulatório de puericultura. Recife (PE) Brasil - Low, Sandra Trindade [UNESP] (2015)
Objective: To evaluate oxidative stress, nutritional status and fat soluble vitamins in children in a childcare. Methods: Cross-sectional study with 100 healthy children CISAM / UPE between 20 and 36 months, through the oxidative stress markers, serum levels of antioxidant nutrients, sociodemographic characteristics, nutritional and clinical status. The results are expressed by percentages and statistical measures. This study was approved by the CEPCISAM by Platform Brazil, opinion 946,241. Results: CAH was increased in children with higher income, adequate BMI, more than 120 days of exclusive breastfeeding and correlated inversely with the weight and BMI. The MDA was greater in children below 24 months. One third of the children had some nutritional disorder according to BMI / I, there was a low frequency of consumption of fruits and vegetables and serum beta-carotene below normal. It was found low compliance childcare queries in relation to the recommended by the Ministry of Health. Conclusion: the childcare service is important, their actions are necessary and crucial for the children to present proper growth and development, prevent nutritional disorders and stress framework oxidative throughout his life